SUSTAINABLE TRANSPORT INDICATORS (Perner's Contacts, 2016)
This article is focused on sustainable transport issues. In sustainable transport there still exist adequation gap between observed phenomena and indicators used in practice. The objective of this contribution is to provide an overview of indicators that are monitored on international level by significant international organizations, and they are also monitored on the national level. In the final section of this contribution the obtained findings are evaluated and an impulse for further research is submitted.
Keywords: sustainable transport; indicators; transport policy